Learning on the IGT follows emergence of knowledge but not differential somatic activity - Fernie, Gordon; Tunney, Richard J. (Frontiers in Psychology, 2013)
The importance of unconscious autonomic activity versus knowledge in influencing behaviour on the Iowa Gambling Task (IGT) has been the subject of debate. The tasks developers, Bechara and colleagues, have claimed that behaviour on the IGT is influenced by somatic activity and that this activity precedes the emergence of knowledge about the task contingencies sufficient to guide behaviour. Since then other have claimed that this knowledge emerges much earlier on the task. However, it has yet to be established whether somatic activity which differentiates between advantageous and disadvantageous choices on the IGT is found before this point. This study describes an experiment to determine whether knowledge sufficient to guide behaviour precedes differential autonomic activity or vice versa. This experiment used a computerised version of the IGT, knowledge probes after every 10 trials and skin conductance recording to measure somatic activity. Whereas in previous reports the majority of participants end the task with full conceptual knowledge of the IGT contingencies we found little evidence in support of this conclusion. However, full conceptual knowledge was not critical for advantageous deck selection to occur and most participants had knowledge sufficient to guide behaviour after approximately 40 trials. We did not find anticipatory physiological activity sufficient to differentiate between deck types in the period prior to acquiring this knowledge. However, post-punishment physiological activity was found to be larger for the disadvantageous decks in the pre-knowledge period, but only for participants who displayed knowledge. Post-reward physiological activity distinguished between the advantageous and disadvantageous decks across the whole experiment but, again, only in participants who displayed knowledge and then only in later trials following their display of knowledge.